KESANTUNAN BAHASA WHATSAPP MAHASISWA TERHADAP DOSEN PRODI PENDIDIKAN BAHASA INDONESIA DI UNIVERSITAS INDRAPRASTA PGRI - Astuti Samosir (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This research was conducted in 2018/2019 in Indonesian Language Program, Universitas Indraprasta PGRI, started in October 2018 until January 2019. This Source of data is messages sent by under graduate students through WhatsApp to Indonesian Language program lecturers, Universitas Indraprasta PGRI. Tehnique of recording data were reading and comphrending each chat between under graduate students and their lecturers through screenshoot. Analysis was conducted based on politeness principles and intrepreted their application and of politeness principles violence. The result showed if under graduate students of Universitas Indraprasta PGRI have used six politeness principles explained